2018
DOI: 10.1590/s0034-759020180105
|View full text |Cite
|
Sign up to set email alerts
|

Deficit De Alfabetização Financeira Induz Ao Uso De Empréstimos Em Mercados Informais

Abstract: Deficit de alfabetização financeira induz ao uso de empréstimos em mercados informais Déficit de educación financiera induce el uso de préstamos en mercados informales ABSTRACTFinance literature documents associations between a family's financial literacy and its propensity to borrow. However, most studies focus exclusively on formal loan markets. Based on 2,023 observations about financial behavior of Brazilian families, we examined the impacts of financial literacy on informal borrowing, such as loans from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…In the worst-case scenario, individuals who bought a capitalization bond have 57% more chance of having a derogatory mark. This result is consistent with Santos et al (2018), who found that capitalization bonds are the worst fixed income security that an individual can buy in Brazil and only financially illiterate individuals would acquire this asset. Thus, financially illiterate individuals would be more prone to delaying their payments and having a derogatory mark.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the worst-case scenario, individuals who bought a capitalization bond have 57% more chance of having a derogatory mark. This result is consistent with Santos et al (2018), who found that capitalization bonds are the worst fixed income security that an individual can buy in Brazil and only financially illiterate individuals would acquire this asset. Thus, financially illiterate individuals would be more prone to delaying their payments and having a derogatory mark.…”
Section: Resultssupporting
confidence: 91%
“…Financial illiteracy is measured by the acquisition of capitalization bonds. Santos et al (2018) argue that investing in a capitalization bond is irrational. They use the real example of holding a 36-month capitalization bond with a yield of 3.36% p.a.…”
Section: Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on financial literacy focus on diverse variables, such as age, education level, region, marital status, professional situation, income, training in economics/finance, experience and knowledge in finance, job and work (Bannier and Schwarz, 2018; Fonseca et al. , 2012; Santos et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Being financially knowledgeable is a fundamental requirement for the effective growth of today's society, improving the economic-financial well-being and supporting social inclusion. Different individuals do not make the same financial decisions because these depend on a set of sociodemographic factors (Bannier and Schwarz, 2018;Fonseca et al, 2012;Santos et al, 2018). Therefore, this article aims to identify the profile of the Portuguese regarding the perception of financial literacy, that is, it intends to answer the following research questions: How many profiles of financial literacy perception is it possible to find in the Portuguese population?…”
Section: Introductionmentioning
confidence: 99%